Historical Biogeography and the Evolution of Hematophagy in Rhodniini (Heteroptera: Reduviidae: Triatominae) - de Paula, Alexandre Silva; Barreto, Carlos; Telmo, Mike Cerqueira Martins; Diotaiuti, Lileia; Galvão, Cleber (Frontiers in Ecology and Evolution, 2021)
The Rhodniini tribe is one of the five tribes in the subfamily Triatominae (Hemiptera: Reduviidae) and is notorious for its domestic blood-sucking pests and vectors of Trypanosoma cruzi Chagas across Latin America. The human and economic cost of the Chagas disease in the American tropics is considerable, and these insects are of unquestionable importance to humans. We used mitochondrial rDNA (16S) and nuclear ribosomal RNA (28S) sequences to perform phylogenetic analysis to derive trees based on parsimony and maximum likelihood. Nucleotide sequences were used in molecular clock analyses to estimate time divergence between species of Rhodniini. The potential distribution of each species was modeled and compared with Kappa statistic. Multivariate niches with bioclimatic variables were used to describe differences between the species using discriminant analysis. The results of this study indicate that the Rhodniini originated 26.64 Mya ago. R. domesticus is the oldest species having its origin at 19.57 Mya. Most species are clearly allopatric and have distinct bioclimatic niches. The colonization of bromeliads, palms trees, and bird nests represent important events for the speciation of these taxa. The hematophagous lifestyle can be described as a scenario where Rhodniini's ancestor could be pre-adapted for the invasion of bromeliads, palm trees, and bird nests where they would find significant water availability and thermal damping. These environments are widely used by vertebrate inquilines that would be the source of food for the species of Rhodniini